1982
DOI: 10.1159/000207072
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alpha-1-Acid-Glycoprotein, Haptoglobin and C<sub>3</sub> in Hodgkin’s Disease

Abstract: 107 determinations of α1-acid-glycoprotein (α1S), haptoglobin (Hp) and complement fraction 3 (C3) were made in 85 consecutive patients with Hodgkin’s disease, both in acute phase (77 measurements) and in complete remission (30 measurements). Only α1S and Hp showed much higher levels in untreated disease than in remission, and elevation of α1S in activity of the disease is correlated to advanced stages and – less significantly – to severe histology. The abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies, in fact, have shown that there was no difference in survival between women who have had a therapeutic abortion compared with those who have not 12–14 . A higher incidence of advanced stage cases has been found during pregnancy, 15–17 probably because the early signs of HL such as fatigue, vomiting, abdominal pain may be superimposed on the discomforts of pregnancy 17 . Furthermore, in a large Swedish population study, the incidence of HL after the first 6 months after delivery seemed to be higher, probably because the disease was diagnosed only after the end of pregnancy 15 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies, in fact, have shown that there was no difference in survival between women who have had a therapeutic abortion compared with those who have not 12–14 . A higher incidence of advanced stage cases has been found during pregnancy, 15–17 probably because the early signs of HL such as fatigue, vomiting, abdominal pain may be superimposed on the discomforts of pregnancy 17 . Furthermore, in a large Swedish population study, the incidence of HL after the first 6 months after delivery seemed to be higher, probably because the disease was diagnosed only after the end of pregnancy 15 …”
Section: Introductionmentioning
confidence: 99%